2015
DOI: 10.12735/jbm.v4i3p16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Justice Perception on Organizational Commitment among Healthcare Sector Employees

Abstract: This study aims to examine the relationship between organizational commitment and organizational justice perceptions of employees working in private healthcare institutions in Van province. Within this purpose, the data was obtained through a questionnaire administered to 300 employees of four hospitals in Van. To measure the organizational justice perceptions of the employees, the organizational justice scale with three constructs was used, and their organizational commitment was measured with the organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…This means that an increase in an organisational justice has the strong possibility to improve teachers' job commitment. This finding is in line with previous studies such as Gichira et al, (2016); Gulluce at al., (2015); Buluc and Gunes (2014); Akanbi and Ofoegbu (2013) in their empirical studies revealed that there was a significant relationship between organizational justice and teachers' commitment. When teachers perceive their head teacher to be fair, respectful and unbiased in his or her dealings, they are likely to exhibit positive work outcomes such as commitment and dedication.…”
Section: Discussion Of Resultssupporting
confidence: 94%
“…This means that an increase in an organisational justice has the strong possibility to improve teachers' job commitment. This finding is in line with previous studies such as Gichira et al, (2016); Gulluce at al., (2015); Buluc and Gunes (2014); Akanbi and Ofoegbu (2013) in their empirical studies revealed that there was a significant relationship between organizational justice and teachers' commitment. When teachers perceive their head teacher to be fair, respectful and unbiased in his or her dealings, they are likely to exhibit positive work outcomes such as commitment and dedication.…”
Section: Discussion Of Resultssupporting
confidence: 94%
“…Research from the past has shown that how workers feel about organizational justice has a big effect on their attitudes, such as job satisfaction and organizational commitment; work engagement (Jami and Agha, 2022); performance (Pan et al ., 2018); and work-related behaviors, such as entrepreneurial intention (Urban and Moloi, 2022); and organizational citizenship and absenteeism (Colquitt et al ., 2001). Workers with a positive perception of organizational justice are committed more to their organization, affecting job satisfaction and organizational accomplishment (Turgut et al ., 2012). Cropanzano and Greenberg (1997) found that a lack of organizational justice leads to negative attitudes and actions at work, such as job dissatisfaction, low level of commitment, less cooperation, low performance, low morale and plans to leave the job.…”
Section: Introductionmentioning
confidence: 99%